The role of asad dilmurod in modern uzbek romanticism - Khasanov Haydar Rustamovich (Research Parks Publishing LLC, 2021)
This article describes the role of the unique writer Asad Dilmurod in modern Uzbek literary criticism. That is, in the literary process, certain opinions are expressed about his works, which cause controversy. The article concludes about the formation of the individual style of the writer